Theory and applications of non-integer order systems : 8th Conference on Non-integer Order Calculus and Its Applications, Zakopane, Poland /: 8th Conference on Non-integer Order Calculus and Its Applications, Zakopane, Poland. ([2017]) - Unknown
No abstract available